Strategi Pembelajaran Differentiated Instruction Untuk Mengatasi Perbedaan Kemampuan Siswa Dalam Pembelajaran Pai Di Sma Ma’arif Nu Mambaul Ulum Pucuk: Differentiated Instruction Strategies for Addressing Student Ability Diversity in Islamic Education at Ma’arif NU Mambaul Ulum Senior High School, Pucuk - Emilia Refianti; Siti Suwaibatul Aslamiyah; Nurul Azizah (Prodi PAI, Fakultas Tarbiyah, UNIDA GONTORs Tarbiyah, Universitas Darussalam Gontor, 2025)
Differentiated learning is a strategy designed to adapt to differences in initial abilities during learning. With this approach, students are given space to develop their potential optimally. Thus, the role of teachers becomes increasingly crucial in adjusting learning strategies to meet the needs of each individual in the class. When conducting research observations, data is obtained in the form of a phenomenon showing that students there have different learning comprehension abilities. For that reason, teachers in that context, especially Islamic Religious Education teachers, innovate in learning by implementing differentiation strategies in Islamic Religious Education subjects. It is hoped that the learning process can provide experiences that align with the individual needs of each student, enabling them to develop their potential optimally. This study aims to determine the implementation and results of differentiated instruction learning to overcome differences in student abilities in Islamic Religious Education at SMA Ma'arif NU Mambaul Ulum Pucuk. This study uses a descriptive qualitative approach. The results of the research data show that the implementation of this differentiated learning has a positive effect on students because they can learn based on their learning styles or preferences, and they create projects such as mind mapping or slide shows as a result of their learning. They also dare to present their work to build their confidence and skills.